Analysis of Consumer Preferences in Assessing the Attributes of the Marketing Mix of RCTI's Live Streaming - Christanti, Dyah; Eddyono, Fauziah (PT Mattawang Mediatama Solution, 2025)
Over the past decade, RCTI's live television viewership has tended to decline although it experienced an increase, particularly during the Covid-19 pandemic. This decline in traditional media viewership is particularly pronounced in entertainment programs and news broadcasting. Programs that were once exclusively accessible through traditional media can now be accessed on various digital platforms. This study aims to analyze whether consumer preferences, especially those of Generation Z, who are highly connected to technology, have shifted from watching RCTI television to using digital platforms. Based on conjoint analysis, the results show that 96 respondents from Generation Z in Jabodetabek still prefer to watch entertainment, sports, and news programs broadcast during fixed hours. This finding suggests that RCTI should focus on maintaining consistent broadcast schedules and continue innovating in content production to remain competitive in the increasingly crowded broadcasting industry.